FACTORS OF FORMATION OF THE PROFESSIONAL ACTIVITY OF STUDENTS OF THE FIELD OF SPECIAL EDUCATION IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE IN HIGHER EDUCATION INSTITUTIONS - M. Tursunova (Journals Park Publishing, 2023)
Knowledge of languages in socio-political, agricultural, and other areas of Uzbekistan's development becomes a necessary component of a person's personal and professional life, and the requirements of government and society for the results of linguistic preparation should be expressed in their ability to use the languages studied in real intercultural communication
Keywords: factoring, learning foreign languages, integration, education, multilingualism.